2000
DOI: 10.1080/089030600263085
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of P Forms in Natural and Fertilized Forest Soils of the Central Western Spain: Plant Response to Superphosphate Fertilization

Abstract: Soil responds dynamically to the addition of phosphates by establishing exchanges among the di †erent reservoirs of P existing in the soil. T he aim of this work was to Ðnd out the e †ects of surface applied fertilization with triple superphosphate at two concentrations (50 and 100 kg P ha ] 1 ) in soils of the Sierra de Gata mountains (Spanish Central System) on forms of soil P, the availability of P for plants, and the impact on aboveground production of the tree cover and grasses. Soil P was deter ± mined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The distribution of P among different organic and inorganic forms reflects the history, present structure, and function of an ecosystem [15,32].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of P among different organic and inorganic forms reflects the history, present structure, and function of an ecosystem [15,32].…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviations for the rest of the parameters are lower and the significant differences observed in the limed subplot in relation to the no-limed one should be attributed to the effect of liming (except for the available P, given that availability of P is also influenced by other soil properties, as the soil pH, inputs of organic residues, and/or the presence of free sesquioxides [15].…”
Section: Characteristics Of the Soil Studiedmentioning
confidence: 99%
“…It was previously demonstrated that the soil sesquioxides (Fe and Al) quickly precipitated the dissolved P [34,35,40,15]; as a result of this, it is not possible to improve the availability of soil P with the sole addition of liming material. Komljenovic et al [41] found that liming influenced the annual production yields, but so did the climatic factors; given the low dissolution process of the CaCO 3 added, it is difficult to think that the dissolved liberated Ca 2+ could have more impact than the sesquioxides.…”
Section: Evolution Of the Soil Parameters In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rainfall and runoff (slopes frequently higher than 30%) permit that acidif ication remains in these deciduous forest ecosystems (Gallardo et al, 1998b;Moreno & Gallardo, 2002). In addition, in spite that the decomposition of litter (Table 2) is relatively fast, the N is retained by the decomposing litter (Gallardo et al, 1998b), the P availability by plant is very low (Turrion et al, 2000), and the stability of the humic substances (calculated soil-humus decomposition-constant is 0.026, Table 3) is high.…”
Section: Annual Biomass Increasementioning
confidence: 99%